Development of youth entrepreneurship in the Russian Federation - A. Fedorova; E. Astakhova; E. Krivokora (Вестник Северо-Кавказского федерального университета, 2022)
The article presents some aspects of the analysis of the current situation in the field of youth entrepreneurship. The results of sociological research, including in the Stavropol Territory, are considered. The problems of the development of youth entrepreneurship in the Russian Federation and possible negative consequences are identified. The model of youth entrepreneurship development management is proposed, which will ensure the competent functioning of all government structures in the field of development and support of youth entrepreneurship, the creation of an effective public administration system within the framework of the implementation of youth policy in the field of youth entrepreneurship.